The Dialectics of Tradition: Negotiating Habitus and Field in the Persistence of the Mantu Kucing Ritual among Agrarian Communities - Hesti Amelia Mawardani; FX Sri Sadewo; Kholida Ulfi Mubaroka; Permata Ayu Widyasari (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2026)
The Mantu Kucing, or ‘cat marriage,’ ritual in Curahjati Village, Banyuwangi, Indonesia, stands as a significant traditional practice that reflects the spiritual responses of agrarian communities to ecological uncertainty. Passed down through generations, this ritual was historically a means to invoke rain, yet it now confronts challenges posed by modernization, scientific rationality, and climate change. Although academic discourse surrounding traditional rain-making beliefs has expanded, systematic research on the social reproduction mechanisms that support their persistence remains limited. This study explores how the meanings and functions of Mantu Kucing are expressed in community life and how traditional beliefs are negotiated alongside modern meteorological knowledge. Employing Pierre Bourdieu's social practice theory, this qualitative ethnographic research analyzes the interactions among habitus, field, and symbolic capital. Conducted in Curahjati Village, the research involved interviews with ten informants, comprising traditional leaders, farmers, religious figures, and youth, as well as participant observation and documentation. The findings reveal that Mantu Kucing operates as a complex mechanism for social reproduction, where the ritual habitus engages with various overlapping fields: traditional rituals, Islamic practices, modern scientific knowledge, and the market economy. The ritual serves not only as a spiritual expression of cosmological beliefs but also as a means of fostering social solidarity through gotong royong (mutual cooperation). Additionally, it acts as a source of symbolic capital that enriches cultural identity and provides a venue for negotiating authority between traditional and modern knowledge systems. The tradition persists through strategic adaptation, maintaining its spiritual essence while embracing digital documentation and actively engaging younger generations by reinterpreting the ritual as local wisdom. This study underscores how agrarian communities exercise cultural agency within structural constraints, effectively preserving their collective identity through creative transformation and offering alternative rationalities for navigating ecological uncertainty.